2020
DOI: 10.21037/atm-20-1579
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in neuroendocrine disorder-related candidate genes associated with pre-pregnancy obesity in gestational diabetes mellitus patients by using a stratification approach

Abstract: Background: Certain candidate genes have been associated with obesity. The goal of this study is to determine the association between thirteen neuroendocrine disorder-related candidate genes and prepregnancy obesity among gestational diabetes mellitus (GDM) patients using the stratification approach defined the Asian and International criteria-based body mass index (BMI).Methods: This was a post-hoc case-control exploratory sub-analysis of a cross-sectional study among GDM women to determine which candidate si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Additionally, 32 transcripts were identified for TEX51 . A study of the genetic association between obesity and the TEX51 [ 55 , 56 ] neuroendocrine disorder-related candidate gene suggested a lack of any correlation between TEX51 and maternal obesity and reported that the highest number of transcripts of any TEX was recorded for TEX51 , indicating the potentially critical function of this gene in male cattle reproductively. Hence, in-depth functional studies are warranted in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 32 transcripts were identified for TEX51 . A study of the genetic association between obesity and the TEX51 [ 55 , 56 ] neuroendocrine disorder-related candidate gene suggested a lack of any correlation between TEX51 and maternal obesity and reported that the highest number of transcripts of any TEX was recorded for TEX51 , indicating the potentially critical function of this gene in male cattle reproductively. Hence, in-depth functional studies are warranted in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Many environmental, nutritional and genetic factors are related to the development of GDM, which potentiates the stress condition/ symptomatology of pregnancy. Among the genetic factors, OXTR & MNTR1B single nucleotide polymorphisms (SNPs) have been of particular focus 22 . Although, there are studies that found an association between OXTR & MNTR1B SNPs gestational diabetes while other studies documented involvement of OXTR & MNTR1B SNPs in psychological disorders like depression, anxiety and/or stress we could not find out studies in our population which have evaluated the association of the above given genetic risk factors with stress development in GDM.…”
Section: Discussionmentioning
confidence: 99%